p53 immunostaining pattern is a useful surrogate marker for TP53 gene mutations - You-Na Sung; Deokhoon Kim; Jihun Kim (BMC, 2022)
Abstract Background TP53 is the most frequently mutated gene in the human cancer, and the awareness of its mutational status is useful in the diagnosis and treatment of cancer patients. In the present study, we investigated the association between TP53 gene mutations and p53 immunohistochemical staining (IHC) patterns and non-genetic effect of MDM2 as a negative regulator of p53. Methods A total of 135 solid cancer cases with next generation sequencing data were subjected to p53 IHC and classified as overexpression, null type or usual pattern. Results TP53 mutation was observed in 104 out of 135 cases (77.0%). When the TP53 mutations were annotated into DISRUPTED (truncations, frameshifts, splice site mutations, and deep deletions) and IF-DBD (in-frame mutations in the DNA binding domain), the null type p53 IHC pattern was associated with DISRUPTED mutations (sensitivity 86.2%, specificity 97.2%) while the overexpression pattern was associated with IF-DBD mutations (sensitivity 100%, specificity 81.7%). The specificity of p53 IHC usual pattern predicting wild type TP53 was also as high as 100%. Regardless of MDM2 amplification, p53 IHC pattern showed a perfect association with TP53 mutation pattern. Conclusions p53 IHC pattern (overexpression, null type, usual) reasonably predicted TP53 mutational status (DISRUPTED, IF-DBD), and MDM2 amplification status did not have any impact on the p53 IHC pattern.